2020
DOI: 10.1074/jbc.ra119.011025
|View full text |Cite
|
Sign up to set email alerts
|

Conformation-specific inhibitors of activated Ras GTPases reveal limited Ras dependency of patient-derived cancer organoids

Abstract: The small GTPases H, K, and NRAS are molecular switches indispensable for proper regulation of cellular proliferation and growth. Several mutations in the genes encoding members of this protein family are associated with cancer and result in aberrant activation of signaling processes caused by a deregulated recruitment of downstream effector proteins. In this study, we engineered variants of the Ras-binding domain (RBD) of the C-Raf proto-oncogene, Ser/Thr kinase (CRAF). These variants bound with high affinity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…By contrast, a minimal fragment (CR1) comprising RBD and CRD of Raf-1 was successfully generated using bacterial expression system and utilized to examine a potential interaction with Rsu-1. Our quantitative assessment with BLItz biosensor system revealed that while Raf-1 CR1 domain significantly bound HRAS (G12V) that is consistent with recent binding study ( 46 ), it did not interact with Rsu-1 at a physiologically meaningful affinity (data not shown), suggesting that the CR1 does not involve the binding site for Rsu-1. Confirmation of a potential physical interaction between Raf-1 and Rsu-1 and the presence of additional as-yet-uncharacterized linker molecules should await further investigation until a full-length Raf-1 protein and a diverse set of interactors become available.…”
Section: Resultssupporting
confidence: 88%
“…By contrast, a minimal fragment (CR1) comprising RBD and CRD of Raf-1 was successfully generated using bacterial expression system and utilized to examine a potential interaction with Rsu-1. Our quantitative assessment with BLItz biosensor system revealed that while Raf-1 CR1 domain significantly bound HRAS (G12V) that is consistent with recent binding study ( 46 ), it did not interact with Rsu-1 at a physiologically meaningful affinity (data not shown), suggesting that the CR1 does not involve the binding site for Rsu-1. Confirmation of a potential physical interaction between Raf-1 and Rsu-1 and the presence of additional as-yet-uncharacterized linker molecules should await further investigation until a full-length Raf-1 protein and a diverse set of interactors become available.…”
Section: Resultssupporting
confidence: 88%
“…Soft randomization means that in each codon triplet encoding the target amino acid, the wt nucleotide occurs with a probability of 70%, while the remaining 30% are evenly distributed among the three non-wt nucleotides. For a library of 19 residues, such an approach results in a mild mutational load of five to six mutations on average, which not only maintains the overall folding of the LC3 proteins but also introduces sufficient surface variations required for a subtle optimization of existing intermolecular contacts (Ernst et al, 2013;Wiechmann et al, 2017Wiechmann et al, , 2020. After mutagenesis, our final combinatorial libraries contained in average 6.5 × 10 9 unique variants of LC3B or GATE-16 displayed on filamentous phage.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we describe the protein engineering of specific inhibitors of LIRs and characterize their binding properties in vitro and their impact on the survival of THP-1 cells, a model cell line to study acute myeloid leukemia (AML). We predicated our protein engineering approach on previous work where we demonstrated that intracellular affinity reagents can be generated by introducing targeted mutations in the binding site of a naturally occurring binding partner (Ernst et al, 2013;Wiechmann et al, 2017Wiechmann et al, , 2020. As scaffold to target LIRs, we chose the proteins LC3B and GATE-16 from the LC3/GABARAP family of LIR-binding proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular variants of naturally occurring binding partners developed by phage display have been widely used as effective tools for studying PPI functional epitopes, interrogation of signaling pathways, and monitoring of intracellular pathway activity (Ernst et al, 2013;Gorelik et al, 2016;Stolz et al, 2017;Wiechmann et al, 2017Wiechmann et al, , 2020Zhang et al, 2016). We anticipate that integrating protein engineering and chemical screening has the potential to expand the targetability of other therapeutically relevant but challenging targets.…”
Section: Discussionmentioning
confidence: 99%